Elucidation of the role of solvents on the growth of urea / Nurshahzanani Shahrir - Shahrir, Nurshahzanani (2024)
The shape of drug crystals plays a crucial role in the downstream processing in pharmaceutical manufacturing. Difficulties may arise when dealing with unwanted crystal shapes, leading to challenges in manufacturing processes such as during filtration, granulation, and tabletting. Consequently, this affects the overall quality of the final products. In this work, the crystal growth and morphology of urea, its associated solubility in various solvents, and growth kinetics were investigated using experimental and molecular modelling approaches. The solubility of urea crystals was found to be most soluble in water and less soluble in alcoholic solvents. The urea crystals grown in polar protic solvents by cooling crystallisation were found to be of αform, as confirmed by powder X-ray diffraction, differential scanning calorimetry, and Fourier transform infrared spectroscopy analyses.